Vulnerability of adolescents to sexually transmitted infections - Rezende, Raisa Evaly Alves de; Davoglio, Rosane Silvia; Oliveira, Caroline Ferreira de; Viana, Acássio dos Santos Amorim; Silva, Artur Alves da; Nascimento, Ananda Ariane Januário do; Davoglio, Tárcia Rita (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: Adolescents are especially susceptible to sexually transmitted infections, with approximately 1/7 of all new cases of human immunodeficiency virus infection in this group. Objective: To investigate the vulnerability to sexually transmitted infections among adolescents of the Centers for Testing and Counseling for Sexually Transmitted Diseases / Aids, CTAs, in the city of Juazeiro, state of Bahia, Brazil, from 2006 to 2012. Methods: This was an exploratory cross-sectional study that used secondary data from 1,173 adolescents. Data analysis was processed in Stata 9.0 software by descriptive statistics and Pearson’s χ2 test. Results: There was predominance of female adolescents (56.86%), brown (22.85%), single (80.22%), with 8–11 years of education (44.76%) and stable partner (56.78%). The prevalence of sexually transmitted infections was of 5.88%, and there was statistically significant association with sex (more prevalent among girls; p=0.014), education (more common among the less educated; p=0.031) and marital status (more frequent among married/common-law; p=0.036). Conclusion: Safer sex practices and later start of sexual activity combined with empowering actions, especially girls’, are important steps to reduce sexually transmitted diseases among adolescents.